Individual And Generalized Lyric Hero (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article is devoted to a comprehensive analysis of the concepts of the individual and generalized lyric hero in poetic works. The study examines the relationship of the lyric hero with the author’s “I,” its subjective and typical characteristics, as well as its poetic functions. Through examples from classical and modern poetry, it is shown that the individual hero reflects the personal mental state and inner experiences of the author, while the generalized hero represents the social mindset, universal ideas, and typical feelings of a particular historical period. Comparative-typological, structuralist, hermeneutic, and biographical methods form the methodological basis of the study. The results demonstrate the scientific significance of analyzing the lyric hero in both individual and generalized forms and its practical value in literary analysis and education
Keywords: lyric hero; individual hero; generalized hero